2010
DOI: 10.1016/j.clim.2009.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Parameters for establishing humanized mouse models to study human immunity: Analysis of human hematopoietic stem cell engraftment in three immunodeficient strains of mice bearing the IL2rγnull mutation

Abstract: “Humanized” mouse models created by engraftment of immunodeficient mice with human hematolymphoid cells or tissues are an emerging technology with broad appeal across multiple biomedical disciplines. However, investigators wishing to utilize humanized mice with engrafted functional human immune systems are faced with a myriad of variables to consider. In this study, we analyze HSC engraftment methodologies using three immunodeficient mouse strains harboring the IL2rγnull mutation; NOD-scid IL2rγnull, NOD-Rag1n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
256
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 240 publications
(276 citation statements)
references
References 40 publications
13
256
1
Order By: Relevance
“…24 To determine whether the efficient human cell engraftment in the NOD strains was completely dependent on the NOD-type SIRPA polymorphism, we compared the engraftment efficiency of the BRGS mouse with the NOD-RG mouse as a control, because in both strains RAG and ␥c genes are disrupted to disturb lymphoid cell development. The NOD-RG strain displays the excellent human cell engraftment comparable to the NOG/NSG strain 21 in which the SCID mutation instead of RAG-1 disruption is introduced. Our data show that the reconstitution activity of human hematopoiesis in BRGS mice is at least equal to that in NOD-RG mice in terms of engraftment levels and multilineage reconstitution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 To determine whether the efficient human cell engraftment in the NOD strains was completely dependent on the NOD-type SIRPA polymorphism, we compared the engraftment efficiency of the BRGS mouse with the NOD-RG mouse as a control, because in both strains RAG and ␥c genes are disrupted to disturb lymphoid cell development. The NOD-RG strain displays the excellent human cell engraftment comparable to the NOG/NSG strain 21 in which the SCID mutation instead of RAG-1 disruption is introduced. Our data show that the reconstitution activity of human hematopoiesis in BRGS mice is at least equal to that in NOD-RG mice in terms of engraftment levels and multilineage reconstitution.…”
Section: Discussionmentioning
confidence: 99%
“…For example, within the SCID strain, the SCID with the NOD background was the gold standard for the xenotransplantation assay based on its high efficiency. 11 In fact, recent studies have shown that among the lymphoid-depleted mouse strains, the NOD-scid Il2rg null (NSG/NOG) 14,15 and NOD.Rag1 null Il2rg null (NOD-RG) 20 strains are the most efficient; the BALB/c.Rag2 null Il2rg null (BALB-RG) strain is the next efficient 21,22 ; and the C57BL/6 strains with scid, 23 Rag2 null , Rag2 null B2m null , Rag2 null Prf null , 24 or Rag2 null Jak3 null25 mutations are unable to reconstitute human hematopoiesis. The NOD strain has multiple immune deficiencies, including defects of appropriate regulation of the T-lymphocyte repertoire, antigen presenting cell function, NK cell function, 26 and hemolytic complement (C5) and cytokine production from macrophages, 27 and these abnormalities are presumed to collaborate to cause the development of autoimmune diabetes and hemolytic anemia.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Since the early 2000s, immunodeficient mice appropriate for generating humanized mice have been successively developed by introducing the mutant IL2rc gene into NOD/SCID and RAG1/2 null mice by backcross mating, thus resulting in NOD/SCID/cc null mice 11,12 and Rag1/2 null cc null mice. [13][14][15][16] These mice show multiple immunodeficiencies, including defects in T, B and natural killer (NK) cells, and reduced macrophage (Mw) and dendritic cell (DC) function. 11 In these mice, extremely high human cell engraftment rates and increases in well-differentiated human multilineage hematopoietic cells from human hematopoietic stem cells (HSCs), as compared with parent immunodeficient mice, were observed.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of the injection route and age, intrahepatic or intravenous injection (through the facial vein) into newborn mice and intravenous injection (via the tail vein) into adult mice were generally used. 11,14,21 Brehm et al 16 examined various parameters, including injection route, injection age and immunodeficient mouse strains. By comparing engraftment rates of human cells from HSCs, they concluded that intrahepatic injection of HSCs into newborn mice enhanced engraftment as compared with adult mice.…”
Section: Introductionmentioning
confidence: 99%
“…After transfer into these mice, human HSPCs can develop into most of the hematopoietic lineages and the human chimerism is maintained for several months (5,8). Overall the composition of engrafted cells is similar in these models but higher human engraftment levels were obtained in NOD-based models (10). This advantage is thought to be caused at least partially by a polymorphism in the gene encoding the inhibitory receptor signal regulatory protein alpha (SIRPa) (11).…”
mentioning
confidence: 99%